2022
DOI: 10.3390/agronomy12040789
|View full text |Cite
|
Sign up to set email alerts
|

Grocery Waste Compost as an Alternative Hydroponic Growing Medium

Abstract: Modern hydroponic substrates have contributed significantly to the popularity and progress of hydroponic cultivations worldwide, nevertheless, their development, transportation, and disposal often come at a significant environmental cost. Here we investigate the feasibility of partial to total replacement of conventional organic growing media constituents, such as cocodust (C), in a 20% perlite (P) and 80% cocodust substrate (hereafter control 8C), with compost from locally sourced grocery waste (W). For this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 53 publications
1
4
0
Order By: Relevance
“…Similar to our results, Moschou et al [70] found that in hydroponic lettuce (Lactuca sativa var. Tanius) cultivation waste-based compost (from fruits, and vegetable and olive pruning) substrate significantly increased leaf dry weight (19.8%) of the plants compared to the conventional organic growing media constituents (cocodust).…”
Section: Effect Of Growing Medium On the Growth And Yieldsupporting
confidence: 93%
“…Similar to our results, Moschou et al [70] found that in hydroponic lettuce (Lactuca sativa var. Tanius) cultivation waste-based compost (from fruits, and vegetable and olive pruning) substrate significantly increased leaf dry weight (19.8%) of the plants compared to the conventional organic growing media constituents (cocodust).…”
Section: Effect Of Growing Medium On the Growth And Yieldsupporting
confidence: 93%
“…A porous medium has adequate pore space to allow water and air to move more flexibly. It reported that planting medium with high porosity could increase the mung bean's lateral root length and shoot its dry weight (Kusuma et al, 2013;Moschou et al, 2022;Thalib, 2019). Increasing soil porosity can increase plant growth (Anastasia et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The results can be partially attributed to the increased water availability of perlite:coir and perlite compared to pumice, but mainly to the significantly increased organic nitrogen (%) concentration of the leaves in perlite:coir and perlite compared to pumice and sole coir. Correspondingly, Moschou et al [82] investigated the effect of grocery waste compost on the growth parameters of lettuce plants, and according to the results, grocery waste-based compost led to a significant increase in leaf area (cm 2 ) compared to perlite and coir substrate.…”
Section: Vegetation Characteristics and Physiological Parametersmentioning
confidence: 99%